2019
DOI: 10.1016/j.chemosphere.2019.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial visualisation of food contaminant distributions: Polychlorinated naphthalenes (PCNs), potentially toxic elements (PTEs) and aflatoxins

Abstract: This is a repository copy of Geospatial visualisation of food contaminant distributions: Polychlorinated naphthalenes (PCNs), potentially toxic elements (PTEs) and aflatoxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…However, the PCNs concentrations in muscle and liver tissues were lower than those reported in previous studies [110][111][112] . Penta-CNs were dominant in both muscles and gonads, constituting 55.6% and 39.8%, respectively, similar to the results from previous studies on various fish samples [81,108,113,114] . Zhihua et al [115] also analysed PCNs concentrations in 75 different fish species from UK, Ireland and France.…”
Section: Fishsupporting
confidence: 89%
“…However, the PCNs concentrations in muscle and liver tissues were lower than those reported in previous studies [110][111][112] . Penta-CNs were dominant in both muscles and gonads, constituting 55.6% and 39.8%, respectively, similar to the results from previous studies on various fish samples [81,108,113,114] . Zhihua et al [115] also analysed PCNs concentrations in 75 different fish species from UK, Ireland and France.…”
Section: Fishsupporting
confidence: 89%
“…Aflatoxin B1 (AFB 1 ) is considered the most significant risk factor among mycotoxins and the most frequently found aflatoxin in contaminated foods and feed [5][6][7]. Due to its stability and heat-resistant nature, not all food processing methods are efficient at removing AFB 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Data on abiotic media showed PCNs decreasing in sediment cores from the UK with peaks in 1980and in 1960s (Gevao et al, 2000. A similar study on two sediment cores from the Jiaozhou Bay (Yellow Sea) showed that PCN contamination within the Bay decreasing from the elevated levels in the early 1990s, to 34.9 pg g -1 dm around 2000, while outside the Bay the peak levels of the mid-1970s decreased in later years up to the late 1990s (Pan et al, 2012).…”
Section: Pcn #70 Time Trends and Compositional Relevancementioning
confidence: 99%